2020
DOI: 10.1590/s1980-220x2018048903590
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence and frailty syndrome in hypertensive older adults

Abstract: Objective: To analyze the association between adherence to antihypertensive treatment and frailty syndrome in hypertensive older adults. Method: A descriptive, cross-sectional study with a quantitative approach with older adults. The data collection took place between November 2017 and March 2018, evaluating sociodemographic information, adherence to antihypertensive treatment, lifestyle and frailty through the Edmonton Frail Scale. The Kruskal-Wallis test and the Chi-squared test were used for data analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
1
0
3
Order By: Relevance
“…O Plano de Ações Estratégicas para o Enfrentamento das Doenças Crônicas Não Transmissíveis prioriza o controle e combate da HAS por meio de ações de promoção e proteção à saúde (BRASIL, 2011). Além disso, a Estratégia de Saúde da Família, a expansão da atenção farmacêutica e distribuição de medicamentos pelo governo brasileiro têm possibilitado aos pacientes com HAS melhorias na sua assistência e acompanhamento (SILVA et al, 2013). A DM foi auto-referida por 24,7% dos sujeitos analisados no estudo, assemelhando aos resultados de outra investigação (CANUTO, NOGUEIRA, ARAÚJO, 2016).…”
Section: Resultsunclassified
“…O Plano de Ações Estratégicas para o Enfrentamento das Doenças Crônicas Não Transmissíveis prioriza o controle e combate da HAS por meio de ações de promoção e proteção à saúde (BRASIL, 2011). Além disso, a Estratégia de Saúde da Família, a expansão da atenção farmacêutica e distribuição de medicamentos pelo governo brasileiro têm possibilitado aos pacientes com HAS melhorias na sua assistência e acompanhamento (SILVA et al, 2013). A DM foi auto-referida por 24,7% dos sujeitos analisados no estudo, assemelhando aos resultados de outra investigação (CANUTO, NOGUEIRA, ARAÚJO, 2016).…”
Section: Resultsunclassified
“…The purpose of this work was to assess the relationship between frailty and compliance with therapeutic recommendations and cooperation in elderly patients with hypertension; only a few studies have attempted to analyze this dependence so far, and their results are inconclusive. A Brazilian study of hypertensive older adults [38] demonstrated no association between frailty and adherence to antihypertensive treatment. In contrast, the study of Jankowska-Polańska et al [39] showed that frailty negatively affected adherence in elderly hypertensive patients, and lower adherence to the recommendations was diagnosed more often in frail patients than in nonfrail patients [40].…”
Section: Discussionmentioning
confidence: 96%
“…A boa adesão dos idosos à terapia anti-hipertensiva. Fazendo a análise entre escolaridade e o tempo de uso do tabaco, Silva et al, (2020) concluiu que a escolaridade surge como um fator de grande relevância, pois quanto mais anos de estudo o idoso tem, melhor é o grau de adesão ao tratamento anti-hipertensivo. No que se refere ao hábito de fumar, foi observado que…”
Section: Fatores Que Facilitam a Adesão Dos Idosos à Terapia Anti-hipertensivaunclassified
“…De acordo com Silva et al, (2020), apesar dos dados encontrados mostrarem resultados satisfatórios no que diz respeito ao processo de aceitação da medicação anti-hipertensiva, alguns fatores ainda prevalecem no processo de não adesão ao tratamento medicamentoso. Como visto em outros estudos sobre o tema, a baixa renda e o aumento de doenças relacionadas ao processo de envelhecimento contribuem para que a adesão não ocorra conforme o esperado.…”
Section: Fatores Que Dificultam a Adesão Dos Idosos à Terapia Anti-hipertensivaunclassified